Antimicrobial activities of Desi Cow Dung Extracts against human pathogens and phytochemical analysis using chloroform extracts - Nayak, Arabinda; Gohel, Shivani (International Journal of Advanced Chemistry, 2019)
The main objective is to examine the anti-microbial properties and Photochemical screening of the cow dung extracts which are useful to kill the pathogens in humans.Nowadays there is increasing microbial drug resistance problem, so new alternative to synthetics drugs are explored. Along with it antimicrobial activities of natural products are in search. Study of anti-microbial activities of desi cow dung extracts of chloroform against microorganisms namely E. coli and K. Pneumonia.Also the phytochemical analysis for the flavonoids, glycosides, steroids, tannins and phenol compounds. The antimicrobial sensitivity test by disk diffusion method and the disk made from the cow dung showed the zone of inhibition in the petri-plates of both the microorganisms namely E. coli and K. Pneumonia.The phytochemical analysis also showed colour change and precipitation except the phenols. As the microorganisms are becoming resistant to the antibiotics and synthetic drugs, new alternate natural drugs can be explored and used against several diseases caused by this microorganisms.Â Â